Hydration habits in elite futsal players during official games - Garcia-Jimenez, J. V.; Yuste, J. L.; Garcia-Pellicer, J. J.; Perez-Jorge, J. A.; Lopez-Roman, F. J. (Japanese Journal of Physical Fitness and Sports Medicine, 2011)
Futsal is a variant of soccer that is played on a smaller playing surface and mainly played indoors. It is played between two teams of five players, and unlimited substitutions per team are permitted. The purpose of this study has been to determine the body water balance and level of dehydration in field futsal players from an elite team during competition. Eight male elite futsal players (mean±SD: age: 23.5±4.5 yrs; weight 76.5±6.8 kg; height 1.80±0.12 mt) participated in the present study during six official games (Ta; 22-26 °C, RH; 32-42.33%) from the first division league in Spain. Sweat loss was calculated by the body weight looses in pre- and post-game after collection of fluid intake and urine loss. Mean fluid intake (FI) was 1.6±0.7 L. consuming 71.0±33.3% of total fluid loss. The body weight loss was 0.7±0.8 Kg, equivalent to a level of dehydration (DH) of 0.9±1.1%, which is not related to a reduction in performance. There are no significant differences in FI and DH results obtained between the games (p>0.05). We conclude that, in the players from the analyzed team, hydration status can be seen to maintain itself through regular substitutions and the correct level of fluid intake. However, data allow for an individualisation of player's hydration strategies.